Ownership of Oil and Gas in Nigeria: A Need for Paradigm Shift? - Adoga-Ikong, J. Adams; Ibekwe, Adaeze Favour (Universitas Negeri Makassar, 2021)
Nigeria is one of the Africanâ€™s largest producers of crude oil. The current capacity of oil production stands between 250-300 million barrels per day. Unfortunately, the country has been and is being going through a lot of crisis especially in the oil producing areas of Nigeria, the reason being that the ownership of oil being in the hands of the state (Federal Government of Nigeria) right from the colonial era to date has brought a lot of dissatisfaction, ill or mistreatment, neglect and under development among the people where the oil is produced. There are various legislations in Nigeria including the present 1999 Constitution of the Federal Republic of Nigeria which confer the ownership and control of oil and gas in the Federal Government of Nigeria. This research is therefore, to examine these extant laws that confer ownership in the Federal Government and see if there are problems vis-Ã -vis the various agitations by the indigenes of the oil producing areas and see if there will be a need for paradigm shift in the ownership. This will be done by looking at other jurisdictions where oil is produced and if possible to suggest the best practice rule for Nigeria for a peaceful environment in the oil producing areas of Nigeria.